The Relationship of Emotional Intelligence to Basic Locomotor Movements in Early Children - Wati, Yuning Eka Rahma; Jaya Sumantri, Riyan; Irwanto; Anggoro Dwi Cahyo (Yayasan Insan Mulia Bima, 2024)
The background of this research on basic movements for children is one thing that is important in children's lives, as a provision for life in the future. Not a few children whose basic movements are not optimally developed. There are also children whose movement development is in accordance with their age level but in reality, there are errors in carrying out these movements. The purpose of this study is to analyze: 1) The relationship of emotional intelligence to the ability of locomotor basic movements in RA children. This study uses a quantitative approach with a correlation design. The sample used was RA Ma'arif 1 Metro students totaling 78 students. The data collection techniques used were (1) Scale, (2) Documentation, (3) Observation. This research results: 1) there is a significant relationship between emotional intelligence and locomotor movements in RA children at 0.006 <0.05. Based on the results of the study, it can be concluded that there is a significant relationship between the ability of emotional intelligence to locomotor basic movements in RA children. Implications: 1) Adding to researchers' knowledge related to factors that have a significant effect on children's basic locomotor movements. 2) Improve their behavior and attitudes in a more positive direction, so that they are able to control emotions and be able to overcome problems.